Internet service providers as subjects of prevention of sexual crime on the Internet - A. K. Zharova (Правоприменение, 2023)
The subject of the article is the provisions of the legislation of the Russian Federation aimed at ensuring the sexual inviolability of a minor.The object of the research is the relations connected with ensuring the sexual inviolability of minors.The Internet serves as an additional tool that facilitates access to minors, their social pages, the impact on the psyche of minors, and the involvement of children in destructive groups. However, not all articles establishing criminal liability for violation of the sexual inviolability of children contain a qualifying feature - this is the use of the Network in the implementation of such activities. Thus, Art. 135 of the Criminal Code of the Russian Federation, which establishes criminal liability for committing indecent acts against minors, does not contain a qualifying feature - the commission of a crime through the use of the Internet.The organization of Internet relations on the Web is carried out by various Internet providers, whose activities are connected both with organizing the communications of network users and with ensuring the circulation of information on the Internet. Based on these theses, the article provides answers to such questions as can acts were committed with the help of Internet technologies to be qualified under Art. 135 of the Criminal Code of the Russian Federation, is the use of Internet technologies by ISPs effective as a tool to combat crimes against the sexual integrity of minors carried out using the Web, and what legal and technical instruments will ensure the sexual integrity of children?The study showed that the norms of the Criminal Law aimed at preventing crimes related to the sexual inviolability of minors are also applicable to acts committed using the Internet. In accordance with the legislation of the Russian Federation, violence can take the form of physical or mental impact on a person, carried out through the Internet. Regarding the possibility of committing indecent acts on the Web, it can also be concluded that such acts can be recognized as depraved, despite the absence of direct physical contact with the body of the victim.States use various methods for determining the content, recognizing images distributed on the  Web.  The  most  commonly  used  technological  tool  is  the  information  monitoring method. However, the obligation to use this method, both in Russia and in European countries, is not provided for all types of hosting providers.In connection with the analysis of Russian legislation, we can conclude that the possibilities of such hosting providers as the owners of audiovisual services and news aggregators in the field of information monitoring remained unused. Thus, the Federal Law “On Information, Information Technologies and Information Protection” does not contain requirements for the owners of audiovisual services and news aggregators to conduct mandatory monitoring of information distributed on Internet platforms.The use of content filtering technology cannot be considered a panacea, but its mandatory use by various hosting providers will reduce the likelihood of distributing prohibited information.The requirement for the owners of social networks to monitor content by their users, defined by the Federal Law “On Information, Information Technologies, and Information Protection”, is only the first step taken towards reducing the volume of prohibited content posted on the Web. However, the requirements for the use of image and text recognition technologies by Internet providers remained outside.The article used the methods and techniques of formal logic - this is analysis and synthesis, analogy, comparison, hypothesis, proof in order to determine assumptions and find answers to the questions posed in the article.The study and comparative analysis of the practice of ensuring the safety of children from information posted on the Web, reflected in foreign studies, demonstrating possible solutions, made it possible to compare Russian experience with the experience of foreign colleagues and draw conclusions about approaches to solving the problems.The methods of forecasting and modeling are used for formulating possible ways to develop regulation and eliminate gaps in Russian legislation.